2021
DOI: 10.1080/00221309.2021.1878485
|View full text |Cite
|
Sign up to set email alerts
|

Worry during the initial height of the COVID-19 crisis in an Italian sample

Abstract: In the earliest months of 2020, the COVID-19 emergency reached a pandemic status of international concern. In this situation, people tended to think more about current difficulties and their negative consequences due to the fear of infection and changed daily life during quarantine. The aim of this study was to explore the severity of worry in relation to individual characteristics and emotions during COVID-19 outbreak in the Italian people. Socio-demographic questions and standardized self-report questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 120 publications
7
46
0
Order By: Relevance
“…The exposition of a serious threat for physical safety enhances the perception of health risk for themselves and for significant others (Cava et al, 2005) and, consequently, distress. In line with such considerations, our findings suggests that COVID-19 exposure increased the worry perception (Sebri et al, 2021) which, in turn, was associated with higher distress. This result is consistent with the literature (Gudykunst & Nishida, 2001), which identifies high uncertainty as a risk factor for the development of negative psychological mental health.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The exposition of a serious threat for physical safety enhances the perception of health risk for themselves and for significant others (Cava et al, 2005) and, consequently, distress. In line with such considerations, our findings suggests that COVID-19 exposure increased the worry perception (Sebri et al, 2021) which, in turn, was associated with higher distress. This result is consistent with the literature (Gudykunst & Nishida, 2001), which identifies high uncertainty as a risk factor for the development of negative psychological mental health.…”
Section: Discussionsupporting
confidence: 87%
“…Besides contingent and external factors, such as the exposure to COVID-19, other factors might influence individuals' level of distress during pandemic, such as individual differences in personality (Mazza et al, 2020;Morelli et al, 2020), dispositions (Conversano et al, 2020;Rossi et al, 2020;Sebri et al, 2021), and coping strategies (Prout et al, 2020). Literature indicates that individual differences in the ability to tolerate ambiguous situations (e.g.…”
Section: The Effect Of Intolerance Of Ambiguity On Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…759 respondents (out of a total sample of 1233) of the initial survey (Sebri et al, 2021) expressed their consent to participate in a follow-up study, gave email addresses, and were contacted to fulfill the next phase. 436 agreed to take part and complete the first follow-up evaluation but only 177 completed both the first (T1) and the second follow-up evaluation (T2).…”
Section: Participantsmentioning
confidence: 99%
“…Qualitative research based on the critical incident technique (Durosini et al, 2021) showed that healthy citizens were able to experience also positive events during the lockdown (e.g., in terms of cultivation and enjoinment of relationships with loved ones), but at the same time they were subjected to notable emotional distress: for example, the daily experience of the lockdown, along with the alarming messages coming from the media and the unreal perception of emptiness and isolation in the cities, were connected to a novel "sensation of emergency" accompanied by everlasting negative arousal. Likewise, research showed that people with higher perception of COVID-19 severity and lower perception of control over the possibility of infection reported higher levels of worry and anxiety (Sebri et al, 2021). A longitudinal study (Pellerin and Raufaste, 2020) demonstrated how psychological resources created a buffer against the negative effects on well-being.…”
Section: Introductionmentioning
confidence: 98%